Opportunities for digital tracking technologies in the precast concrete sector in Sweden - Shehu, Maryam Olaoti; Almeida, Roma; Mahapatra, Krushna (Frontiers in Built Environment, 2025)
The construction sector is a major consumer of natural resources and a significant contributor to environmental degradation through resource depletion, waste generation, and greenhouse gas emissions. As the industry shifts toward sustainable and circular practices, improving material traceability and resource efficiency becomes crucial. Digital Tracking Technologies (DTT) offer a promising solution, yet their adoption in the precast concrete sector remains limited, necessitating an in-depth examination of influencing factors. This study explores DTT adoption in Sweden’s precast concrete industry, addressing a critical gap in understanding how digital technologies support Circular Economy (CE) objectives. By identifying key barriers and drivers, the research provides a holistic view of the challenges and opportunities shaping this transition. A mixed-methods approach was employed, integrating bibliometric analysis, social media sentiment analysis, and stakeholder interviews. Data analysis was conducted using VOS Viewer, Orange Data Miner, and NVivo, while findings were interpreted through a sociotechnical lens. The study utilizes PESTLE and SWOT analyses within the Multi-Level Perspective (MLP) framework to examine dynamics at the niche, regime, and landscape levels. Findings highlight systemic barriers such as high investment costs, fragmented infrastructure, limited knowledge, and cultural resistance. However, opportunities exist, including enhanced operational efficiency, improved information dissemination, CE alignment, supportive policies, and targeted incentives. Innovations like RFID tags, QR codes, and Digital Product Passports can enhance material traceability and circularity. Given regime inertia and landscape pressures, cohesive policy interventions and industry collaboration are essential. This study provides actionable insights for industry stakeholders, policymakers, and sustainability advocates to advance digital innovation and sustainable construction practices.